Is the Rise in the Prevalence of Renal Replacement Therapy at Older Ages the Price for Living Longer? - Peters, Frederik; Westphal, Christina; Kramer, Anneke; Westerman, Ronny (Frontiers in Public Health, 2018)
Background: Renal replacement therapy (RRT) is one of the most expensive in renal medicine. Cross-sectional studies suggest that life expectancy increases in the general population are associated with a higher burden of RRT. This paper tests this hypothesis in a prospective setting among people aged 75+ living in Western Europe. Methods: We gathered sex-specific data for 11 Western European countries in 2005-2014. RRT prevalence on country-level was extracted from the ERA-EDTA registry, while data on population size and life expectancy for the 75+ age group came from the Eurostat database. GDP per capita was extracted from the OECD database. To measure the association between RRT prevalence and life expectancy, we performed Poisson regression models separately for each country and for all countries combined. To adjust for confounding, GDP per capita as well as time and country fixed effects were included. Results: Our analysis revealed that living longer coincides with rising RRT prevalence at ages 75+ in Western Europe between 2005 and 2014. On average, a one-year increase in life expectancy was associated with a roughly 20% increase in RRT prevalence ([95% CI] 21% to 23% in men and 19% to 22% in women). However, after adjustments for confounding were made, the association became insignificant among women and became weaker among men, falling to a level of 11% ([95% CI] 6% to 17%). Conclusion: Living longer was not necessarily associated with a higher burden of RRT in Western European countries.